IMPLEMENTATION OF WORK DISCIPLINE IN IMPROVING EMPLOYEE PERFORMANCE IN THE DISCIPLINARY SECTION OF PERUM PERURI - Rafika Indra Pratama; Wike Pertiwi; July Yuliawati (Jurnal Mantik, 2022)
This study aims to analyze and describe the implementation of work discipline in improving employee performance in the Disciplinary Section of Perum Peruri. This research involves employees in the Discipline Section through literature studies, case studies, and portfolio documents from research activities. The results of this study indicate that employees' non-compliance with company regulations causes problems not being on time, causing empty absences in the Employee Self Service (ESS) system because company regulations are not implemented regarding late permits or leaving the company for personal purposes which can affect employee performance. . Based on the results of qualitative descriptive analysis, it can be concluded that the enforcement of discipline is important for companies as a basis for improving employee performance, because discipline contains rules that must be obeyed by employees. Discipline is expected to make work as efficient as possible which can provide benefits for both the organization and employees.